A GIS- Based Fire-Response Efficiency Analysis – Benghazi (Journal of Technology Research, 2025)
Cities in Libya face fundamental challenges in firefighting due to the absence of fire hydrant networks, which are widely recognized as the global standard for providing rapid and direct water access during emergencies. Instead, urban areas rely entirely on fire trucks as the sole source of water supply, creating serious limitations in both response speed and firefighting efficiency. This study develops an analytical model designed to evaluate the effectiveness of fire response in environments lacking hydrant systems and dependent exclusively on mobile water carriers, as is the case in Libya. The proposed model integrates GIS with routing algorithms to simulate the dispatch of fire trucks. It further compares the actual water delivered with the required demand in accordance with international standard such as NFPA 1141. The model also estimates the number of vehicles required, water efficiency index, and visualizes results through interactive dashboards and isochrone-based coverage maps. The model was applied to Benghazi using logistical data, including the current single fire station, 32 residential neighborhoods, estimated water demand, and travel times. Data were processed using Python-based GIS tools. The evaluation included the calculation of response times, assessment of water supply adequacy, and multi-scenario simulations to identify areas meeting or failing to meet standard response requirements. Results showed that only 53% of neighborhoods met the required response thresholds at night, while the percentage dropped to 31.25% during midday, leaving the majority underserved and revealing major gaps in resource allocation and preparedness. The study provides a practical framework that can support decision-makers in proactive planning, with the aim of reducing fire risk and enhancing the sustainability of urban emergency management in contexts without traditional hydrant infrastructure. Furthermore, the model was able to identify the required number and optimize the spatial distribution of fire stations to ensure compliance with standard response times
Keywords: Firefighting systems; Response time; GIS-based assessment; Water demand